2021
DOI: 10.18332/tid/142521
|View full text |Cite
|
Sign up to set email alerts
|

The adverse health effects of waterpipe smoking in adolescents and young adults: A narrative review

Abstract: Waterpipe (WP) smoking has rapidly grown in popularity in the United States and other Western countries with the fastest uptake among younger individuals. This growth has been encouraged by the misperception that WP smoke is harmless or less harmful than cigarette smoke. To better understand how WP affects the health of young people, we conducted a narrative review of the literature focusing on the adverse health effects of WP smoking in adolescents and younger adults. We searched scientific literature databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 104 publications
(239 reference statements)
0
7
0
Order By: Relevance
“…The harmful effects of waterpipe smoking are not restricted to adults, with adverse health effects such as acute lung infection and injury, carbon monoxide poisoning, and subclinical consequences (e.g., lung function decline, oral and systemic genotoxicity, and the alteration of vascular and hemodynamic functions) found among adolescents ( 14 ). Abbadi et al found that waterpipe nicotine dependence was associated with depressive symptoms among adolescents ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The harmful effects of waterpipe smoking are not restricted to adults, with adverse health effects such as acute lung infection and injury, carbon monoxide poisoning, and subclinical consequences (e.g., lung function decline, oral and systemic genotoxicity, and the alteration of vascular and hemodynamic functions) found among adolescents ( 14 ). Abbadi et al found that waterpipe nicotine dependence was associated with depressive symptoms among adolescents ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in this study, the incidence of cytological changes exceeded that of prior research. This may be due to the presence of cigar smokers and individuals who consume toombak, both of whom can induce abnormal changes in oral epithelial cells within the cohort [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forced Expiratory Volume in 1 second (FEV1), Forced Vital Capacity (FVC), and FEV1/FVC Ratio are essential parameters for the diagnosis of obstructive and restrictive pulmonary diseases. Water Pipe smoking results in a significant reduction in FEV1, FVC, and FEV1/FVC ratio (Adetona et al, 2021). Furthermore, Water Pipe smoking increases the probability of developing gastric cancer, even though the mechanism is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, Water Pipe smokers might inhale more smoke than cigarette smokers due to the longer duration of Water Pipe smoking. In addition, one session of Water Pipe smoking is found to be equivalent to smoking 100 cigarettes (Adetona et al, 2021). High concentrations of nicotine, tar, carbon monoxide, and heavy metals are present in the Water Pipe smoke (Taati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%